Pengaruh Teman Sebaya terhadap Perilaku Sosial dan Keberhasilan Belajar Siswa - Basith, Abdul (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Often problems arise, and students in learning absorb different understandings. This is due to the influence of peers on social behavior and student learning achievement. For this reason, when the learning process takes place to be kind to friends and can increase achievement when the learning process takes place to be kind to friends and can increase achievement in learning. In learning, the teacher needs to innovate excitingly. This study aimed to determine how much influence peers have on social behavior at MTs Negeri 1 Kutai Kartanegara and how much influence peers have on student learning achievement at MTs Negeri 1 Kutai Kartanegara. In this article, the researcher used descriptive research with a quantitative approach, with a population of 404 students at MTs Negeri 1 Kutai Kartanegara, and the method used was purposive sampling to obtain a sample of 93 students, collecting data through the distribution of questionnaires and documentation: data validity and reliability testing techniques. Then the data obtained were analyzed using simple linear regression analysis. The results showed that the influence of peers on social behavior and student learning achievement at MTs Negeri 1 Kutai Kartanegara was obtained from the first data. The coefficient of determination was R = 0.829 and formulated as a percentage of the coefficient of determination. It was accepted that the influence of peers on social behavior was 68.7%, and the results of the calculation of the t-test with a significance of 0.000 <0.05, which states that Ho is rejected. Ha is accepted so that it can be noted as